Antistaphylococcal Activity and Phytochemical Analysis of Crude Extracts of Five Medicinal Plants Used in the Center of Morocco against Dermatitis - Ikrame Zeouk; Mounyr Balouiri; Khadija Bekhti (International Journal of Microbiology)
Novel drugs for methicillin-resistant Staphylococcus aureus (MRSA) hospital- and community-acquired infections are needed because of the emergence of resistance against antibiotics. In this study, methanolic and aqueous extracts of Berberis hispanica, Crataegus oxyacantha, Cistus salviifolius, Ephedra altissima, and Lavandula dentata selected from an ethnopharmacological study to treat skin infections in Sefrou city (Center of Morocco) were tested for their antistaphylococcal activity against strains often involved in cutaneous disorders: two methicillin-resistant Staphylococcus aureus strains and one strain of Staphylococcus epidermidis using the well-diffusion assay, while the agar macrodilution method was used to determine the minimal inhibitory concentrations. The total phenolic compounds and flavonoid contents of all tested extracts were also evaluated. Three of the five methanolic extracts showed an important antibacterial activity. Berberis hispanica extract was the most active with a minimal inhibitory concentration of 04.00 mg/ml against all tested strains, followed by Cistus salviifolius and Crataegus oxyacantha extracts containing the highest amounts of total phenols (133.83 ± 9.03 and 140.67 ± 3.17 μg equivalent of gallic acid/mg of extract). However, the aqueous extracts have not shown any activity against the tested strains. The current data suggested that the most active extracts can be a good source of natural antistaphylococcal compounds and warrants further investigations to isolate bioactive molecules.